Leukocyte cell population data as potential markers of COVID-19 disease characterization: leukocyte parameters and COVID-19 - Introcaso, Giovanni; Galotta, Arianna; Bonomi, Alice; Salvini, Laura; Assanelli, Emilio; Faioni, elena maria; Biondi, Maria Luisa (Journal of Medical Biochemistry, 2023)
Introduction The usefulness of leukocyte cell population data (CPD) is currently being investigated. In COVID-19 pandemic several reports showed the clinical importance of blood parameters. Our study aimed to assess CPDs in Sars Cov-2 patients as new disease markers. Methods From February to April 2020 (1st wave) 540 and from September to December 2020 (2nd wave) 2821 patients respectively were enrolled. SARS CoV-2 infection diagnosis was carried out by Multiplex rRT-PCR from nasopharyngeal swabs. CPDs were detected by XN 2000 hematology analyzer (Sysmex Corporation). A comparison between two disease waves was performed. Additionally, C-reactive protein (CRP) and lactate dehydrogenase (LDH) were assayed. Results CPDs were classified into: cell complextity, DNA/RNA content and abnormal sized cells. We detected parameters increased from the reference population for all cell types for both 1st and 2nd wave (p≤ 0.03). However, in the 2nd vs 1st wave 5 CPDs vs 9 CPDs were found. In addition we observed higher CPD values of the 1st compared to 2nd wave: (NE-SFL) (p=00004), (LY-Y) (p≤0.0001), (LY-Z) (p≤0.0001), (MO-X) (p≤0.0001), (MO-Y) (p≤0.0001). These findings were confirmed by the higher concentrations of CRP and LDH in the 1st vs 2nd wave: 17.3 mg/L (8.5-59.3) vs 6.3 mg/L (2.3-17.6) (p=0.0003) and 241.5 UI/L (201-345) vs 195 UI/L (174-228) (p=0.0005)(median, interquartile range) respectively. Conclusion Leukocyte CPDs showed increased cell activation in patients of 1st wave confirmed by clinical and biochemical data, correlated with worse clinical conditions. Our results highlighted the CPDs as disease characterization markers or useful for a risk model.